Expression of CK-19 and CEA MRNA in peripheral blood of gastric cancer patients - Kutun, S.; Celik, A.; Kockar, M. Cem; Erkorkmaz, U.; Eroglu, A.; Cetin, A.; Erkosar, B.; Yakicier, C. (Experimental Oncology, 2010)
The aim of this paper is to investigate the clinical and pathological relevance of detection of circulating tumor cells (CTC) in the peripheral blood of gastric carcinoma patients before operation.